1997
DOI: 10.1001/archsurg.1997.01430310075015
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-Assisted Resection of Rectosigmoid Carcinoma

Abstract: The immediate and medium-term results of laparoscopic-assisted resection of rectosigmoid carcinoma are promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 14 publications
(1 reference statement)
3
62
0
3
Order By: Relevance
“…1; log rank = 0.8112). Comparable short-term (3-5 years) survival rates were also reported by Fleshman et al [33], Schwandner et al [14] as well as Leung et al [34]. Long-term results of prospective randomized trials are not available despite these promising findings.…”
Section: Oncological Safetymentioning
confidence: 81%
See 1 more Smart Citation
“…1; log rank = 0.8112). Comparable short-term (3-5 years) survival rates were also reported by Fleshman et al [33], Schwandner et al [14] as well as Leung et al [34]. Long-term results of prospective randomized trials are not available despite these promising findings.…”
Section: Oncological Safetymentioning
confidence: 81%
“…These authors therefore concluded that laparoscopic colectomy should only be performed within prospective trials to evaluate the oncological safety of this surgical approach [8] as it has also been suggested by the American Society of Colon and Rectal Surgeons [9]. The data published so far, nonetheless, indicate that the oncological results of laparoscopic surgery compare well with the results of the conventional open approach [10][11][12][13][14][15]. Until now, the available trials assessing the value of laparoscopy in colorectal cancer, however, lacked sufficient statistical power due to small numbers of patients or had short follow-up periods which did not allow proper evaluation of the oncological safety [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is important is to preserve the parasympathetic sacral nerve roots from S2 to S4. Dissection proceeds down to the pelvic floor [75][76][77][78][79][80][81][82][83][84][85][86][87][88].…”
Section: (100% [Strong Consensus]; Gor C: 100% [Strong Consensus])mentioning
confidence: 99%
“…The rectum is transected at the level of the pelvic floor by means of a roticulating endostapler device [75][76][77][78][79][80][81][82][83][84][85][86][87][88], using as few cartridges as possible. Use of more than two cartridges has been reported to result in a higher anastomotic leakage rate [89,90].…”
Section: (100% [Strong Consensus]; Gorb: 100% [Strong Consensus])mentioning
confidence: 99%
See 1 more Smart Citation